Cyber Islamic University dalam Perspektif Hadits Tarbawi - Saidah Khadijah Shabira; Suci Nurdani; Nadia Septyani; Dwi Meutia Hasni (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2026)
This study aims to examine the topic of Cyber Islamic University from the perspective of educational hadith. It highlights the important role of Islamic universities in addressing the shift from conventional education toward a digital model through the innovation of the Cyber Islamic University. This change is undertaken to improve quality and competitiveness without compromising Islamic values and morals. This study employs a qualitative literature review method. The subjects of this study are literature reviews and hadiths discussing cyber-based education. The results of this study indicate thath in the era of globalization, Islamic education is capable of collaborating with the industrial and technological sectors to fulfill the needs of the global community in the digital age. This study demonstrates the novelty that the breakthrough of the Cyber Islamic University is one form of the implementation of Islamic values contained in a number of hadiths of the Prophet Muhammad ?.